(Progressive) Consent, Public Interest in AI, Opt-Out for Secondary Use: New Rules for Scientific Research on Health Data (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper contributes to the debate on European and Italian regulations, both de iure condito and de iure condendo, regarding the construction of subjective legal positions, the balancing of legally relevant interests (both private and public), and the allocation of risks associated with scientific research on health data. The analysis focuses on the following rules: Article 110 of the Italian Data Protection Code, recently amended; Article 8 of the proposed Italian AI Law; and Article 71 EHDS, which introduces the right to opt-out for secondary use. These pages explore their impact on scientific research, highlighting the shortcomings of consent and the risk of regulatory fragmentation.
Keywords: Scientific research; health data; AI; consent; public interest